A two-fold interpenetrating porous metal–organic framework with a large solvent-accessible volume and selective sensing of nitroaromatic explosives. Issue 6 (18th March 2016) - Gong, Yun-Nan; Zhang, Shi-Yong; Xiong, Peng; Xie, Yong-Rong; Du, Zi-Yi; Zhong, Di-Chang
Abstract: A cadmium(II) 3-D porous metal–organic framework, (Me2 NH2 )4 [Cd2 (TTCA)2 Cl2 ]·7DMF·2Diox·6H2 O (1 ) (TTCA = triphenylene-2, 6, 10-tricarboxylate, DMF =  N, N -dimethylformamide, diox = 1, 4-dioxane), has been synthesized through solvothermal conditions. Single-crystal X-ray analysis reveals that the structure of1 has a two-fold interpenetrating framework with a large solvent-accessible volume of 52% per unit cell. The result of topological analysis shows that1 is a (3, 3)-connected 3-D network with {10 3 } topology. Luminescence tests illustrate that1 can selectively sense nitroaromatic explosives via a luminescence quenching mechanism. Abstract :